Renewal of Criminal Law And The Implementation of Chemical Clearance Sanctions For Child Sexual Crimes - Novita Eleanora, Fransiska; Sa'adah, Nur (Devotion : Journal of Research and Community Service, 2022)
Protection of children is an activity to ensure the continuity of their lives to be able to grow and develop as the next generation of the nation, where the protection provided always pays attention to the existence of their rights, both juridical and non-juridical, which aims to ensure that children are always optimally healthy and able to move forward. maturity so that they can support themselves, so that due to protection and children are always guarded to avoid all threats and even actions that can endanger themselves. Because of the importance of protecting children, the perpetrators are always given castration sanctions, namely actions given to perpetrators of sexual crimes against children, in addition to the imposition of sanctions in the form of imprisonment and fines, but for children as perpetrators this chemical castration sanction is excluded. The purpose of this research is to find out how effective the implementation of castration sanctions is as a punishment for perpetrators of sexual crimes. While the method studied from this research is normative juridical, namely reviewing from the literature and also regulations from legislation and relating to the problem under study and can also be done by conducting a literature study where the results are that the implementation of castration sanctions in its application is contrary to human rights, and religion and can disturb the psyche of the perpetrator, and a law that applies nationally and not only a Government Regulation must be made so that its implementation is binding on everyone as an Indonesian citizen wherever they are.